The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/math11030618
|View full text |Cite
|
Sign up to set email alerts
|

A Switchable Chaotic Oscillator with Multiscale Amplitude/Frequency Control

Abstract: For the wide frequency spectrum of chaotic signals, it is difficult to realize chaotic signal conditioning. Therefore, researchers turn to the exploration of chaotic systems with independent non-bifurcation control for easy chaos modification. In this paper, a system with only one non-quadratic term is modified for providing multiscale amplitude/frequency control. By adjusting the feedback with an odd higher degree term, a switchable chaotic oscillator is obtained, which provides the different scales of amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Therefore, it usually has high-security performance in secure communication. So far, there are two main methods to generate the switched system, one is manual switching [21], and the other is automatic switching [22]. Automatic switching does not require human intervention to realize automatic switching between different systems, which can avoid switching failure caused by mechanical switching abnormality.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it usually has high-security performance in secure communication. So far, there are two main methods to generate the switched system, one is manual switching [21], and the other is automatic switching [22]. Automatic switching does not require human intervention to realize automatic switching between different systems, which can avoid switching failure caused by mechanical switching abnormality.…”
Section: Introductionmentioning
confidence: 99%
“…Sha et al designed an encryption algorithm using a hopfield neural network, and the results showed superior performance [21]. Sheng et al proposed a multi-scale adjustment method for the amplitude and frequency of chaotic signals in order to better control chaotic systems [22]. However, as the research progresses, it was found that the maximum Lyapunov exponent of integerorder chaotic systems with the introduction of memory elements was not high enough, leading to the limitation of their chaotic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Chaotic dynamics are encountered in many engineering applications, such as network systems, digital communications, mechanical systems, organic phenomena for example biological populations, and so on [1][2][3][4]. These dynamical systems have several unique characteristics, such as randomness, non-periodicity, and high sensitivity to the initial values.…”
Section: Introductionmentioning
confidence: 99%